Adviser Automation Express: CSV-Powered Multi-Recipient Messaging System (International Journal of Scientific Research in Science and Technology, 2024)
In the ever-evolving realm of digital advertising, the ability to effectively communicate with target audiences is a pivotal determinant of success. Advertisers continually seek innovative solutions to streamline their campaigns, reduce operational overhead, and enhance the personalization of messages to engage consumers more effectively. Manual communication methods, while functional, often fall short in meeting these demands, leading to the exploration automation as a compelling alternative. Adviser automation as a transformative tool for advertisers. Specifically, it focuses on the development and implementation of a CSV integrated message sender, a solution aimed at simplifying the intricate process of reaching audiences at scale.